If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -12z = 9 Solving 8 + -12z = 9 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -12z = 9 + -8 Combine like terms: 8 + -8 = 0 0 + -12z = 9 + -8 -12z = 9 + -8 Combine like terms: 9 + -8 = 1 -12z = 1 Divide each side by '-12'. z = -0.08333333333 Simplifying z = -0.08333333333
| 5-5(3x-2)=-2(x-8)+38 | | f(-9)=3-4x | | 5e^3x-4=2x | | Px-40=Qx+20 | | X^2+18x+67=O | | 17-4z=17 | | 1.8+2.8x= | | 4/5x-1/2=0 | | 8times-2-3= | | 5/3=12/c | | 28/9=42/s | | 32/25=24/z | | 9=b/q | | 9=b/9 | | 20=b/6 | | 1000=x+0.070x | | 1000=x+0.70x | | 8t-7= | | 8-7=17 | | 3(2y-15)=-(y-6) | | 690+1= | | 20logk=14 | | 8-3m=35 | | 9-m=-3 | | X+Y+Z=36 | | x+9=4(5+2) | | 0.4y-6.7+y-0.3-26y= | | 0.4y-6.7+-0.3-26y= | | 6.4c=0.8 | | 6cos^2(x)+7sin(x)-1=0 | | 6x+10+3sinx=0 | | 7p-14=7(p-2) |